Community integration, quality of life, thriving, and mental health among refugees and asylum seekers. A London service provider perspective - Kienzler, Hanna (Frontiers in Public Health, 2024)
Introduction This article explores how systemic injustices and social inequalities affect refugee and asylum seeker integration, thriving, and mental health in London. This is pertinent as the United Kingdom currently operates a ‘broken’ asylum system with unfair policies and a ‘tough’ immigration rhetoric which makes it extraordinarily difficult for asylum seekers and refugees to achieve community integration, have a good quality of life, be able to thrive, and have good health including mental health. Paradoxically, the United Kingdom Home Office also features an Indicators for Integration Framework to provide practical ways to design more effective strategies, monitor services and evaluated integration interventions. Methods This study employed a qualitative research design including semi-structured interviews with 19 mental health and psychosocial support service providers working in third-sector organizations in London. Results The study results show that the current asylum system severely undermines efforts to support asylum seekers and refugees with their integration. All participants highlighted that asylum seekers and refugees lacked experienced poor quality of life and faced structural challenges to build meaningful social connections; to have access education, fair employment and good work; to achieve good mental health and wellbeing; and to be able to thrive. Discussion To improve community integration, quality of life, thriving, and mental health for asylum seekers and refugees in London and, beyond, the United Kingdom, four recommendations are made on structural and service-levels: (1) reform of the current asylum system by centering human rights; (2) implement and carry out needs assessments among asylum seekers and refugees focussing on key social determinants; (3) ensure asylum seekers and refugees benefit from the NHS Inclusion Health framework; and (4) extend the NHS Patient and Carer Race Equality framework beyond England. To be effective, all four initiatives need to be grounded in a participatory approach that meaningfully involves diverse groups of stakeholders including asylum seekers and refugees.